2015
DOI: 10.1007/s10456-015-9467-4
|View full text |Cite
|
Sign up to set email alerts
|

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability

Abstract: Slit2, a secreted glycoprotein, is down-regulated in many cancers. Slit2/Robo signaling pathway plays an important, but controversial, role in angiogenesis. We identified splicing variants of Slit2 at exon 15, Slit2-WT and Slit2-ΔE15, with differential effects on proliferation and invasive capability of lung cancer cells. The aim of this study was to elucidate the differential roles of these exon 15 splicing variants in angiogenesis. Our results revealed that both Slit2-WT and Slit2-ΔE15 inhibit motility of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…While the expression of Slit1 is confined to neurons, Slit2 and Slit 3 are widely expressed in mammalian tissues [ 4 ] and their deregulations have been identified in malignant tissues. Slit2 is frequently inactivated in human cancers including lung cancer [ 5 ], breast cancer [ 6 , 7 ], colorectal cancer [ 8 ], ovarian cancer [ 9 ], glioma [ 10 ] and HCC [ 11 , 12 ] and its tumor suppressive role that inhibits cancer cell invasion and migration [ 10 , 13 17 ], angiogenesis [ 18 , 19 ] and growth [ 8 , 20 22 ], has been well-studied. In conjunction, hypermethylation and subsequent down-regulation of Slit3 has been reported in several cancers, including thyroid cancer, colorectal cancer, gastric cancer, nasopharyngeal carcinoma, cervical cancer, ovarian cancer and pancreatic ductal adenocarcinoma [ 23 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the expression of Slit1 is confined to neurons, Slit2 and Slit 3 are widely expressed in mammalian tissues [ 4 ] and their deregulations have been identified in malignant tissues. Slit2 is frequently inactivated in human cancers including lung cancer [ 5 ], breast cancer [ 6 , 7 ], colorectal cancer [ 8 ], ovarian cancer [ 9 ], glioma [ 10 ] and HCC [ 11 , 12 ] and its tumor suppressive role that inhibits cancer cell invasion and migration [ 10 , 13 17 ], angiogenesis [ 18 , 19 ] and growth [ 8 , 20 22 ], has been well-studied. In conjunction, hypermethylation and subsequent down-regulation of Slit3 has been reported in several cancers, including thyroid cancer, colorectal cancer, gastric cancer, nasopharyngeal carcinoma, cervical cancer, ovarian cancer and pancreatic ductal adenocarcinoma [ 23 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Slit2-WT suppresses lung cancer cell invasion, while Slit2-ΔE15 inhibits both the growth and invasion of lung cancer cells [21]. We also observed that Slit2-ΔE15, but not Slit2-WT, is able to normalize the vessel size [22]. These studies reveal that the Slit2-exon15 splicing forms have differential roles in tumor growth and angiogenesis.…”
Section: Introductionmentioning
confidence: 68%
“…SLIT2 interacts, with its cognate receptor ROBO1 in the human umbilical vein endothelial cells (HUVECs) and tumour-associated endothelial cells 9 . Studies have shown that the ROBO4 receptor imparts inhibitory signal to endothelial migration, tube formation, and vascular permeability through its interaction with SLIT2, suggesting its negative regulatory role in angiogenesis in HUVEC cells 66 68 and an animal model for ocular angiogenesis 69 .…”
Section: Discussionmentioning
confidence: 99%